PENGARUH PRICE DISCOUNT, SERVICE QUALITY DAN SOCIAL MEDIA PROMOTION TERHADAP KEPUASAN KONSUMEN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA MARKET KITAB ASWAJA DI BONDOWOSO - Khusnul Hotimah; Ida Subaida; Triska Dewi Pramitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
As consumer trends and behavior develop, the products offered are required to adapt to changing times. This condition challenges the ASWAJA Book Market in designing marketing strategies to compete optimally with similar MSMEs. This study aims to evaluate the effect of Price discounts, Service quality, and Social media promotions on Consumer Satisfaction, with Purchase Intention as an intervening variable in the Aswaja Book Market. This study applies a quantitative approach with a survey method, where data is collected through distributing online questionnaires to consumers of the Aswaja Book Market. The data analysis technique used is Partial Least Squares (PLS). The results show that Price discounts and Service quality significantly positively affect Purchase Intention. Social media promotions have a positive but insignificant effect on Purchase Intention. Price discounts and Service quality have also been found to positively and significantly affect Consumer Satisfaction. Social media promotions show a positive but insignificant effect on Consumer Satisfaction. In the indirect path, Price discounts, Service quality, and Social media promotions have a positive but insignificant effect on Consumer Satisfaction through Purchase Intention. These findings confirm that price discounts, service quality, and social media promotions significantly shape consumer satisfaction by increasing purchase intention, but this is not yet optimal.